Analysis Of Village Fund Management And Village Fund Allocation (Add) In Improving Village Development In Carawali Village, Sidenreng Rappang Regency - Yayuk Angraeny; Andi AR (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the process of managing Village Funds and Village Fund Allocations (ADD) in improving Village development as well as the constraints faced by the Village government in the process of managing Village Funds and Village Fund Allocations (ADD) in Carawali Village, Sidenreng Rappang Regency. Data collection techniques used in this study are observation, interviews, and documentation. The data analysis techniques used in this study are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of managing Village Funds and Village Fund Allocations (ADD) in improving village development in Carawali Village, Sidenrang Rappang Regency, which consists of planning, implementation, administration, reporting, and accountability has followed the technical instructions stipulated in statutory regulations. -invitation so that it has a very large impact on Village development. The obstacles faced by the Carawali Village government in the process of managing Village Funds and Village Fund Allocations (ADD) in improving Village development, namely delays in disbursing funds caused by delays in preparing the RAB (Budget Budget Plan) and drawing up development drawings, lack of human resources competent and unreliable, and weather conditions so that construction activities are sometimes not completed on time.